Environmental vibration reduction characteristics of subway track with resilient wheel - Sun, Wei; Liu, Linya; Cheng, Gong (Frontiers in Physics, 2025)
Environmental vibrations induced by subway systems are typically mitigated through track-based isolation measures, which are effective only in localized areas. Extending such solutions along entire lines involves prohibitive costs. To address this limitation, this study investigates the application of resilient wheels as a vehicle-based solution for mitigating vibrations across the entire line by controlling excitation at the source. A frequency-domain environmental vibration prediction model coupled with a wheel–rail interaction model is established using the 2.5D FEM–BEM approach. The simulation results are validated against field measurements, confirming the model’s accuracy. Based on the validated model, the influence of key parameters of the resilient wheel, including mass, rubber stiffness, and damping—on environmental vibration is systematically analyzed. The results demonstrate that increasing the mass of the resilient wheel lowers the P2 resonance frequency but leads to a disproportionate increase in wheel–rail force. Reducing rubber stiffness shifts the P2 force toward lower frequencies and reduces environmental vibration by up to 8 dB, while increasing rubber damping effectively suppresses the P2 resonance peak, achieving a maximum vibration reduction of 2.7 dB. This study confirms that resilient wheels offer a technically viable and economically efficient strategy for line-wide environmental vibration control.